Astaxanthin Extraction of Vanname Shrimp (Litopenaeus vanname) Using Palm Oil. Issue 1 (March 2021) - Karnila, R.; Hasan, B.; Ilza, M.; Leksono, T.; Ahmad, M. A.
Abstract: Vanname shrimp is an important economic commodity that has carapace waste which is rich in the pigment astaxanthin. This study aims to determine (1) the chemical composition (proximate) of vanname shrimp carapace flour (2) the astaxanthin content of vanname shrimp carapace flour with different extraction times (3) Randemen of astaxanthin extract of vanname shrimp carapace flour. This research consisted of two stages, namely (1) Preparation and analysis of the chemical composition of vanname shrimp carapace flour (2) Extraction and analysis of the astaxanthin content of vanname shrimp carapace with different extraction times. Experimental research method with completely randomized design (CRD). The different extraction time treatments consisted of three tare, namely 120, 180, and 240 minutes. The data obtained were analyzed using Analysis of Variance (ANOVA). The results showed that carapace flour had a chemical composition of moisture content of 10.28%, ash content of 33.73% db, protein content of 38.82%db, fat content of 1.56%db, crude fiber of 25.9%db. Meanwhile, the highest astaxanthin content from this study was 5.0909 mg / g (240 minutes). the resulting levels were 2.6351 mg / g (120 minutes), 3.2569 mg / g (180 minutes) and 5.0909 mg / g (240 minutes), respectively. The yield of astaxanthin extract produced were 50.95% (120 minutes), 65.36% (180 minutes), and 78.92% (240 minutes), respectively. The highest yield of astaxanthin extract in the study was in the 240 minute treatment of 78.92%.